2011
DOI: 10.1097/btk.0b013e31822ba689
|View full text |Cite
|
Sign up to set email alerts
|

Cementless Fixation in High Performance Knee Design

Abstract: Although cemented fixation in total knee arthroplasty remains the gold standard, new interest in cementless fixation has returned. Earlier implant designs for use in cementless fixation have been associated with high failure rates but newer implants have achieved similar results to their cemented counterparts. This is in part due to advances in the technique and the introduction of new porous materials and design modifications. Cementless techniques can achieve better bony fixation, have less potential for bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
(68 reference statements)
1
3
0
Order By: Relevance
“…The excellent results and a pristine implant-bone interface with no radiolucent lines seen in any TM implants in the present study correspond to what has been reported for the same implant (Milchteim and Unger 2011 , Kamath et al. 2011 , Ghalayini et al.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The excellent results and a pristine implant-bone interface with no radiolucent lines seen in any TM implants in the present study correspond to what has been reported for the same implant (Milchteim and Unger 2011 , Kamath et al. 2011 , Ghalayini et al.…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, several clinical studies have shown excellent clinical results for the TM implants in the 5- to 8-year perspective with very few (if any) revisions due to aseptic loosening (Kamath et al. 2011 , Milchteim and Unger 2011 , Ghalayini et al. 2012 , Fernandez et al.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a cemented TKA has been considered the accepted standard [11,37,40], with predictable and durable results [12,17,21,35,48,53,54]. The survivorship of a welldesigned and properly positioned cemented TKA at 10 to 20 years exceeds 90%, resulting in stability, increased mobility, and reduction of pain for many patients [38,49].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, some authors recommended a hybrid technique using a cemented tibial component and uncemented femoral component [26,47]. However, with time, problems with cementless implants have been overcome by better designs and new fixation systems, reducing the risk of early migration [62] and loosening of the tibial component [18], and resulting in clinical results and survivorship rates comparable to those achieved with cemented implants [5,7,8,18,19,24,25,33,40,46,51,65,66]. However, given the similarity of results, some of these authors have concluded that the lack of advantages of uncemented over cemented components would not support the use of more expensive implants [19,33].…”
Section: Introductionmentioning
confidence: 99%